PENGARUH INFLASI DAN PENDAPATAN ASLI DAERAH (PAD) TERHADAP PERTUMBUHAN EKONOMI KOTA MEDAN - Lubis, Rizal Paruhuman; Handayani, Riska (Universitas Dharmawangsa, 2024)
The study was conducted to analyze the effect of inflation and local original income (PAD) on the economic growth of Medan City. The type of data used in this study is quantitative data in the form of sekuder data derived from data from the Central Bureau of Statistics of Medan City, namely, data on Inflation and Regional Original Income (PAD) and Economic Growth from 2013-2022 using the eviews 10 application. The study used the Vector Autoregressive (VAR) method. The results of the study showed that in the short, medium, and long term variables PE, INF and PAD PE are responded positively in the short and long term by PE itself, responded negatively in the medium and long term by INF. But it was responded positively in the medium term by PAD but in the long term it was responded negatively. INF is responded positively in the short and long term by INF and PE, but is responded negatively in the medium and long term by PAD. PAD is responded positively in the short and long term by PE, responded positively in the long term by the PAD but responded negatively in the short, medium and long term by the INF.